Contemporary food markets within Budapest’s large housing estates: Factors influencing the design process - Dr. habil Melinda Benkő, PhD.; Hlib Antypenko; Anna Kornélia Losonczy (Architecture Papers of the Faculty of Architecture and Design STU, 2021)
Food markets provide a continuous urban function at the centre of urban quarters, and their structures are an important component of the local identity. Therefore, they could be crucial in the complex renewal process of a mass housing neighbourhood, indeed. The paper focuses on the contemporary markets within Budapest’s three large housing estates, in Újpest Centre, Békásmegyer, and Havanna, opened in 2018, 2019, and 2020, respectively. The research is based not only on the study of relevant literature, design documents, publications, fieldwork, but also on a survey conducted with three well-recognized Hungarian architects in order to understand and compare their views on the complex context beyond the urban and architectural solutions. The questions focused on the crucial or determining factors of the design process such as the budget, the main players, references, physical context (built and natural), social context, program, and technology. These public projects of varied scale were used for exemplary contempo-rary food market case studies from Budapest, in which the people involved took into consideration the existing social and material problems and the potential of the heritage of modern mass housing neighbourhoods.